Increasing mine waste will induce land cover change that results in ecological degradation and human displacement - John R. Owen; Deanna Kemp; Alex M. Lechner; Michelle Ang Li Ern; Éléonore Lèbre; Gavin M. Mudd; Mark G. Macklin; Muhamad Risqi U. Saputra; Tahjudil Witra; Anthony Bebbington (Journal of Environmental Management, 2024)

Global assessment of the biodiversity safeguards of development banks that finance infrastructure - Divya Narain; Laura J. Sonter; Alex Mark Lechner; James E. M. Watson; Jeremy S. Simmonds; Martine Maron (Conservation Biology, 2023)
Infrastructure development is a major driver of biodiversity loss globally. With upward of US$2.5 trillion in annual investments in infrastructure, the financial sector indirectly drives this biodiversity loss. At the same time, biodiversity safeguards (project‐level biodiversity impact mitigation requirements) of infrastructure financiers can help limit this damage. The coverage and harmonization of biodiversity safeguards are important factors in their effectiveness and therefore warrant scrutiny. It is equally important to examine the extent to which these safeguards align with best‐practice principles for biodiversity impact mitigation outlined in international policies, such as that of the International Union for Conservation of Nature. We assessed the biodiversity safeguards of public development banks and development finance institutions for coverage, harmonization, and alignment with best practice. We used Institute of New Structural Economics and Agence Française de Développement's global database to identify development banks that invest in high‐biodiversity‐footprint infrastructure and have over US$500 million in assets. Of the 155 banks, 42% ( n = 65) had biodiversity safeguards. Of the existing safeguards, 86% (56 of 65) were harmonized with International Finance Corporation (IFC) Performance Standard 6 (PS6). The IFC PS6 (and by extension the 56 safeguard policies harmonized with it) had high alignment with international best practice in biodiversity impact mitigation, whereas the remaining 8 exhibited partial alignment, incorporating few principles that clarify the conditions for effective biodiversity offsetting. Given their dual role in setting benchmarks and leveraging private finance, infrastructure financiers in development finance need to adopt best‐practice biodiversity safeguards if the tide of global biodiversity loss is to be stemmed. The IFC PS6, if strengthened, can act as a useful template for other financier safeguards. The high degree of harmonization among safeguards is promising, pointing to a potential for diffusion of practices.

Discriminating between large-scale oil palm plantations and smallholdings on tropical peatlands using vegetation indices and supervised classification of LANDSAT-8 - Aslinda Oon; Helmi Zulhaidi Mohd Shafri; Alex Mark Lechner; Badrul Azhar (International Journal of Remote Sensing, 2019)

Recent Progress on Spatial and Thematic Resolution in Landscape Ecology - Alex Mark Lechner; Jonathan R. Rhodes (Current Landscape Ecology Reports, 2016)